Knowledge of integrated management of childhood illnesses community and family practices (C-IMCI) and association with child undernutrition in Northern Uganda - Mukunya, David; Kizito, Samuel; Orach, Tonny; Ndagire, Regina; Tumwakire, Emily; Rukundo, Godfrey Zari; Mupere, Ezekiel; Kiguli, Sarah (Bio Med Central public health, 2014)
Background: Childhood undernutrition is a major challenge in Uganda with a prevalence of wasting and stunting at 5% and 33%, respectively. Community and family practices of the Integrated Management of Childhood Illnesses (C-IMCI) was introduced in sub-Saharan Africa early after the year 2000. C-IMCI was postulated to address major childhood morbidity and mortality challenges with nutrition as one of the outcomes. The association between knowledge patterns of C-IMCI and undernutrition has not been fully established especially in sub-Saharan Africa. This study was done to address the prevalence of stunting and wasting and the association with the knowledge and practices of C-IMCI among caretakers in Gulu district, Northern Uganda. Methods: This was a community-based cross-sectional study among 442 caretaker-child pairs. A standardized questionnaire was employed to assess the knowledge and practices of the C-IMCI among caretakers including four practices: breastfeeding, immunization, micronutrient supplementation and complementary feeding. Weight and height of children (6–60 months) were recorded. Wasting and stunting were defined as weight-for-height and height-for-age z-score, respectively, with a cut-off < −2 according to the World Health Organization growth standards. Logistic regression analysis reporting Odds Ratios (OR) with 95% confidence intervals (CI) was used to explore associations using SAS statistical software. Results: The percentage of caretakers who had adequate knowledge on C-IMCI (basic knowledge within each pillar) was 13%. The prevalence of wasting and stunting were 8% and 21%, respectively. Caretakers’ lack of knowledge of C-IMCI was associated with both wasting (OR 24.5, 95% CI 4.2-143.3) and stunting (OR 4.0, 95% CI 1.3-12.4). Rural residence was also associated with both wasting (OR = 3.1, 95% CI 1.5-6.5) and stunting (OR = 1.7, 95% CI 1.0-2.7). Children younger than 25 months were more likely to be wasted (OR = 3.3, 95% CI 1.7-10.0). Conclusion: We found a low level of overall knowledge of the C-IMCI of 13.3% (n = 59). There is also a high prevalence of childhood undernutrition in Northern Uganda. Caretakers’ limited knowledge of the C-IMCI and rural residence was associated with both wasting and stunting. Interventions to increase the knowledge of the C-IMCI practices among caretakers need reinforcement.
a cross-sectional study
Keywords: Community and family practices of the integrated management of childhood illnesses; IMCI; Stunting; Wasting; Undernutrition; Sub-Saharan Africa; Gulu